Manajemen Sumber Daya Sekolah dalam Pelaksanaan Asesmen Nasional Berbasis Komputer di SD Kristen Piliana Kecamatan Tehoru Kabupaten Maluku Tengah (Studi Kasus) - Murni Daeng Thayb; Rudolf Kempa; Sumarni Rumfot (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
The implementation of the Computer Based National Assessment requires comprehensive school resource readiness. This study aimed to examine resource management at SD Kristen Piliana, Tehoru District, Central Maluku Regency in implementing ANBK. Using a qualitative descriptive method, the study involved principals, teachers, committees, and parents as informants. Findings reveal that resource management remains suboptimal, with lack of electricity and internet access as major constraints. Nonetheless, teacher commitment and collaboration with SMPN 119 serve as key enabling factors. These findings underscore the need for inter-institutional synergy and internal strategy reinforcement. It is recommended that schools and policymakers prioritize infrastructure development and enhance teachers' technical competencies to ensure equitable digital assessment implementation in underdeveloped areas.